Did Canadian welfare reform work? The effects of new reform strategies on social assistance participation. (17th November 2015) - Berg, Nathan; Gabel, Todd
Abstract: This paper measures the extent to which declines in social assistance (SA) participation were associated with novel and aggressive reforms referred to as new reform strategies: work requirements, diversion, earning exemptions and time limits. Controlling for province‐specific benefit levels, eligibility requirements, GDP growth, labour market conditions and demographics, SA participation rates were more than one percentage point lower (equivalent to a 13% decline) in provinces with new reforms. Work requirements with strong sanctions had the sharpest negative associations. New reform strategies explain at least 10% of observed declines in SA participation, twice that of benefit levels and eligibility requirements. Résumé: Est‐ce que la réforme de l'aide sociale est un succès? Les effets des nouvelles stratégies de réforme sur la participation à l'aide sociale . Ce mémoire mesure la taille du déclin de la participation à l'aide sociale (AS) associée aux réformes inédites et agressives qu'on a nommées nouvelles stratégies de réforme: travail requis, diversion vers d'autres programmes, exemptions de gains, et limites temporelles. Normalisés pour tenir compte des niveaux de prestation spécifiques aux provinces, pour les conditions d'éligibilité, pour la croissance du PIB, pour les conditions du marché du travail et la situation démographique, les taux de participation à l'aide sociale étaient plus d'un point de pourcentage plus bas (ce qui équivalait à un déclin de 13 %) dans les provinces à la suite des nouvelles réformes. Les conditions de travail requis et les fortes sanctions attenantes ont eu l'impact négatif le plus fort. Les nouvelles stratégies de réforme expliquent au moins 10 % du déclin dans la participation à l'AS, soit le double de l'impact des changements dans les niveaux de prestation et des conditions d'éligibilité.